1999
DOI: 10.1116/1.581997
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of C4F8 dissociation in parallel-plate-type plasma

Abstract: To investigate the mechanism of C4F8 dissociation in parallel-plate-type plasma, we used several of the latest diagnostic tools and made extensive measurements of electrons, radicals, and ions under conditions that greatly suppressed the effects of plasma-surface interaction. These measurements showed that the amount of light fluorocarbon radicals and ions increased with increasing electron density. The dissociation of C4F8 was analyzed by using rate equations, after confirming the stability and uniformity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 38 publications
5
27
0
Order By: Relevance
“…The triplet IVO wave function was used for all but the 1 1,3 A g pair of states, for which generating the singlet IVO was easier due to technical factors. Examination of the principal configurations in the corresponding SECI wave functions indicates that considering the singlet and triplet wave functions to be identical is a very good approximation for the 1,3 The elastic cross section was first computed at the staticexchange level of approximation. Further calculations incorporating polarization effects were then carried out for irreducible representations exhibiting prominent shape resonances, namely, 2 B 1u , 2 B 2g , and 2 B 2u .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The triplet IVO wave function was used for all but the 1 1,3 A g pair of states, for which generating the singlet IVO was easier due to technical factors. Examination of the principal configurations in the corresponding SECI wave functions indicates that considering the singlet and triplet wave functions to be identical is a very good approximation for the 1,3 The elastic cross section was first computed at the staticexchange level of approximation. Further calculations incorporating polarization effects were then carried out for irreducible representations exhibiting prominent shape resonances, namely, 2 B 1u , 2 B 2g , and 2 B 2u .…”
Section: Computational Detailsmentioning
confidence: 99%
“…3 Detailed understanding of the complex physical and chemical processes within a plasma reactor requires data describing the important collisional and reactive processes occurring both within the plasma and at the semiconductor surface. Among the many processes of interest, elastic and inelastic collisions between electrons and molecules of feed gas are particularly important, because such collisions are the principal mechanism of energy deposition, with the electrons serving to couple the applied fields to the internal and translational modes of the heavy particles and, simultaneously, to create reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the selectivity was governed by not only the absolute value of the F density or the ratio of [F]/[CFx], but also by the other form of deposition species. It is also found that the reduction of the F density in C 4 F 8 /Ar plasma was caused by the decrease in CF 2 density and not by a direct reaction of F with Si when the Si plate was irradiated by energetic ions [19,22].…”
Section: Effect Of Plasma-wall Interactionmentioning
confidence: 87%
“…Upon each electron impact, the molecule dissociates gradually into smaller radicals, i.e., multistep dissociation [19], such as,…”
Section: Electron Impact Dissociationmentioning
confidence: 99%
“…Hayashi et al studied the parallel-plate-type plasma of c-C 4 F 8 using several diagnostic tools including microwave interferometer, laser-induced fluorescence (LIF), infrared diode laser absorption spectroscopy (IRLAS), QMS, etc. [19]. Vasenkov et al [20] explored chemistry mechanism of the inductively coupled plasma of c-C 4 F 8 /Ar and c-C 4 F 8 /O 2 computationally and experimentally.…”
Section: Introductionmentioning
confidence: 98%